Full SiC DCDC-converter with a power density of more than 100kW/dm3 - Kreutzer, Otto; März, Martin; Nakata, Hideki (Materials Science Forum, 2015)
This paper describes a non-isolated bidirectional full SiC 800V 200kW DCDC-converter power stage for electric and hybrid vehicles that reaches a power density of more than 100 kW/dm3 at a switching frequency of 200 kHz. The high power density is achieved by the use of SiC-MOSFETs sintered on custom made Si3N4 DCB-substrates controlled by custom made extremely flat drivers and a resulting very low inductive DC-link connection. All passive components like inductors and capacitor boards are custom made in order to keep all parasitic effects as low as possible. The power is subdivided on six interleaved phases to reduce the required capacitor ripple current capability.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Automotive application; High frequency power converter; High power density systems; Interleaved converters; Power converters for EV; Silicon Carbide (SiC)